Medical Database Security Policies - Pangalos, G. J. (Methods of Information in Medicine, 1993)
Database security plays an important role in the overall security of medical information systems. Security does not only involve fundamental ethical principles such as privacy and confidentiality, but is also an essential prerequisite for effective medical care. The general framework and the requirements for medical database security are presented. The three prominent proposals for medical database security are discussed in some detail, together with specific proposals for medical database security. A number of parameters for a secure medical database development are presented and discussed, and guidelines are given for the development of secure medical database systems.
Keywords: Medical Database Security; Information System Security; Database Security Policies; Database Security